Stroke victim [ rehabilitation (Video Education Australasia / New Zealand Pty Ltd, 2011)
The goal of post-stroke rehabilitation is to enable an individual who has survived a stroke to reach the highest possible level of independence and be as productive as possible. Nurses are integral to the multidisciplinary team responsible for a stroke survivor's rehabilitation program. This comprehensive video-based resource provides nurses with a full overview of their role in post-stroke rehabilitation. With expert insight from a clinical neuropsychologist, occupational therapist, speech pathologist, physiotherapist, and social worker, we provide an overview of stroke and its impacts on the patient, the process of post-stroke rehabilitation, the role of nurses in rehabilitation, and the importance of total patient education.--VEA website